NOTES ON MORPHOLOGICAL CHARACTERISTICS OF EURYCOMA SPP. AND ITS STATUS IN PENINSULAR MALAYSIA - TAN AI LEE; NURNIDA MOHD KAMAL; TAN HOOI POAY; IZLAMIRA ROSLAN (REINWARDTIA, 2015)
TAN, A. L., KAMAL, N. M., TAN, H. P. & ROSLAN, I. 2015. Notes on morphological characteristics of Eurycoma spp. and its status in Peninsular Malaysia. Reinwardtia 14 (2): 259 - 263. - A study had been carried out on the genus Eurycoma Jack that aimed to ascertain the diagnostic characteristics of the two species that occur in Peninsular Malaysia. Samples were collected from 15 localities comprising of forest reserves and plantations throughout Peninsular Malaysia covering the 5 regions i.e. northern, western, eastern, southern and central. The sampling was done to capture the morphological variations from different habitat. In general, morphologically both species were very similar. They could be clearly distinguished using their fertile parts. Eurycoma longifolia Jack had long, drooped inflorescences while in E. apiculata A.W. Benn was usually short, pointed upwards. Small differences were also noted on the leaflet of E. apiculata where the apex of the leaflet was often abruptly pointed while its base was rounded with conspicuous petiolule. On contrary, E. longifolia leaflet apex was usually subacute with its base asymmetrical and decurrent to its petiolule. In addition, anatomical transverse section of E. longifolia leaflet midrib outline and margin were dissimilar with E. apiculata by having convex abaxial surface and blunt tip margin compared to the slightly arc-shape abaxial and tapered margin in E. apiculata. The abundancy of Eurycoma spp. had decreased.